Characterization of a monoclonal antibody recognizing mast cells - De Oliveira Nogueira, T. [UNESP]; Aubin, J. E. (My University, 1997)
Immunohistochemical screening for monoclonal antibodies prepared by immunization of mice with a rat osteoblastic cell population led to identification of one antibody that reacted against a small population of cells present in the soft connective tissue compartment of 21 days fetal rat calvaria. The morphology of the cells and the immunohistochemical staining characteristics (a distinct intracellular granular pattern) suggested that the antibody might be reacting specifically against mast cells. We used combined histochemistry and immunohistochemistry to further characterize this antibody, designated RCJ102. Cryosections containing calvaria bone, soft connective tissues and skin were prepared from the top of the head of 21 days fetal rats, and from adult rats cryosections of lung, muscle, adipose tissue and small intestine were prepared. Some sections were labelled by indirect immunofluorescence with RCJ102; corresponding sections were labelled histochemically with toluidine blue. There was a direct correspondence between mast cells identified histochemically and cells labelling with RCJ102 in all tissues except intestine, in which the mast cell detectable by histochemistry were not labelled by RCJ102. These results suggest that the RCJ102 antibody will be a valuable new reagent for further elucidation of the heterogeneity described between connective tissue and intestinal mucosal mast cells.
Keywords: Connective tissue; Heterogeneity; Immunohistochemistry; Intestine; Mast cells